Islamic History: The Dynamics of Social Reconstruction Towards the Realization of an Egalitarian Society 611-633 AD - Yasir Maulana Rambe; Monika Sari (Universitas Islam Negeri Sumatera Utara, 2026)
Islam always conveys universal messages. It embodies the values of humanity and strong egalitarianism. This study will provide an in-depth examination of traditional Mecca culture and the process of social reconstruction toward an egalitarian society in Mecca, Medina's traditional culture and the process of social reconstruction in Medina, and the relevance of an egalitarian Islamic society in the modern era. This research uses historical research to uncover events that occurred in the past. The noble values of Islam conveyed during the da'wah process in Mecca failed to be realized. Complex problems were the main basis for this failure. The Medina period demonstrated the success of social reconstruction carried out by Islam. Human equality, religious tolerance, social justice, and other human rights were truly upheld. The points of agreement contained in the Medina Charter were truly implemented and adhered to by all residents of Medina at that time. The values of egalitarianism in Islam, the democratic process of social reconstruction, the persistent struggle for humanitarian values, and the consistency and firmness in upholding agreed-upon rules, as practiced by the Prophet Muhammad and his companions in the early Islamic period, both in Mecca and Medina, are concrete examples of what modern societies can do to realize an egalitarian society. Upholding human rights is a necessity, as every human being is inherently born free.